Systematic Literature Review: The Importance of Work Motivation Need for Achievement to Performance - Halim Maimun, Muhammad; Fachrunnisa, Olivia; Ratnawati, Alifah; Mulyana, Mulyana; veno, andri (Benefit: Jurnal Manajemen dan Bisnis, 2025)
The objective of this investigation is to conduct a comprehensive review and synthesis of empirical research regarding the significance of work motivation, specifically the need for achievement, in shaping employee performance in organizational settings. A systematic literature review (SLR) was conducted following the PRISMA guidelines by analyzing peer-reviewed journal articles published between 2020 and 2025 and indexed in Scopus, Web of Science, and Google Scholar. Articles were evaluated according to predetermined inclusion criteria that prioritized employee performance, motivation, and achievement. The review provides robust and consistent empirical evidence that the need for achievement has a positive and substantial impact on employee performance. In comparison to employees with lower achievement motivation, those with high achievement motivation are more likely to establish challenging objectives, exhibit a greater level of task commitment, and produce superior work results. The results reaffirm the ongoing relevance of achievement motivation theory in elucidating performance disparities across a variety of organizational settings and sectors. This study offers a focused contribution by consolidating fragmented findings into a coherent framework and providing an up-to-date synthesis of empirical evidence on the need for achievement and employee performance. It underscores the critical role of achievement-oriented motivation as a primary internal driver of performance and identifies directions for future research, particularly in examining contextual and individual-level moderators.